Institutional condition of reproduction of intellectual capital - Ilona Levina (Cхід, 2013)
The article is discussed the institutional condition of reproduction of intellectual capital. On the basis of the comparative approach examined the development of intellectual capital and factors of building of the knowledge economy. Analysis of external and internal factors of reproduction of intellectual capital in Ukraine has identified the main reasons for the ineffectiveness of development and institutional "traps". There are proposed the recommendations directed to provide an extended reproduction of intellectual capital